Energy-Saving Biomass Stove for Herb Processing of the Wat Khu Tao Moral Herbal Community Enterprise, Songkhla Province - Prasongchan, Somboon; Khaonuan, Palachai; Prasongchan, Nicha (Area Based Development Research Journal, 2021)
The moral herbal community enterprise, Wat Khu Tao, in Songkhla Province, processes herbs for use in Bang Klam Hospital and Community. The former use of traditional stoves and gas cooking stoves resulted in high cost of fuel and production costs. This research, therefore, enhances the quality of the herbal production process of community enterprise by using the technology of energy saving-stove. Processes are as follows: 1) Study of the theory and technology of energy-saving biomass stove; 2) Design and development of energy-saving stove prototype; 3) Development of energy-saving stove technology, and 4) Analysis of thermal efficiency of the energy-saving prototype. The community participated in material preparation and functional testing. The result of the operation shows that the extraction and simmering of herbs took only 40 minutes per time. The production potential of Na Hom Fung Chao balm has increased to 5,400 bottles per month, generating an income of approximately 45,000 baht per month for the community enterprises. Additionally, the creation of a systematic herbal processing network increased to 30 community enterprise members. The application of energy-saving stove technology is also for boiling healthy herbal drinks, which leads to the establishment of a health learning network. In conclusion, the project has successfully promoted energy saving in herb processing, reducing environmental pollution from burning biomass, and passing on the local wisdom to the next generation.